The pathos of freedom and the logos of rationality in Manuel González Prada - Godenzi Alegre, Jorge Luis (2018)
It seeks to determine the relationship bet wean pathos and logos in Don Manuel González Prada, passion rebut essentially libertarian thinker, considered one of the most brilliant exponents of rationalism twentieth century Peruvian. To explain the sap parent paradox examines notions of pathos and logos in the context of positivist philosophy and its vital connection with historicism. We will try to show how the passions a form of knowledge and not an obstacle to achieving levels of objectivity, considering the source of rational activity and not a defect. The pathos for freedom was the beginning of public behavior in Manuel González Prada and the logos of rationality were at his service. In his thought process is described constituent rational conjecture and the prediction, it is concluded that both concepts are clearly connected to his work despite his attempt to make freed on the strongest passion. This voltage sensed inanimate et exits González Prada, who may well be the very essence of literature (not his philosophy), provides one of the most appreciated gifts of his work: that state o faint gravidez, of light nessassui table for sarcasm, irony and the inner smile.  Are the grounds of "discreet pleas rues of intelligence" and "Secret Adventures o forded" said the bright Borges. Rational discourses recreational and therapeutic activities, "laugh terries da round what it denies."